The challenge of liminality for International Relations theory - MALKSOO, MARIA (Review of international studies, 2012)
The concept of liminality favours a broad interpretation, lending itself easily to disciplinary contexts outside of the original framework of cultural anthropology. Developed by Arnold van Gennep and Victor Turner by exploring the rites of passage, liminality points to in-between situations and conditions where established structures are dislocated, hierarchies reversed, and traditional settings of authority possibly endangered. The liminal state is a central phase in all social and cultural transitions as it marks the passage of the subject through ‘a cultural realm that has few or none of the attributes of the past or coming state’. It is thus a realm of great ambiguity, since the ‘liminal entities are neither here nor there; they are betwixt and between the positions assigned and arrayed by law, custom, convention, and ceremonial’. Yet, as a threshold situation, liminality is also a vital moment of creativity, a potential platform for renewing the societal make-up.